Association of Early Postoperative Fall in Albumin with Morbidity after Colorectal Resections - Banepali, Niroj; Adhikari, Subodh Kumar (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Severity of systemic inflammatory response to surgical trauma may predict those at increased risk of postoperative complications. Serum albumin level falls early postoperatively and its measurement is cheap and widely available. This study evaluates the role of postoperative fall in albumin to predict postoperative complications of colorectal resections.Methods: This is a prospective observational study of 56 consecutive patients undergoing colorectal resections in the department of Surgical Gastroenterolgy of Bir Hospital, NAMS from 2020 December to 2022 May. Postoperative albumin drop (Δ Albumin) was defined as ‘Preoperative albumin – Albumin on Postoperative Day 1’. The primary outcome was 30-day postoperative complications. Multivariate analysis was performed to identify factors associated with postoperative complications. Receiver operating characteristic (ROC) curve analysis was done for determining the value of postoperative albumin drop in identifying patients with complications. Results: Postoperative albumin drop > 0.5 g/dl (OR 4.26, CI 3.6-39.99, p = 0.018) and emergency surgery (OR 3.25, CI 1.06-95.79, p = 0.046) were independent predictors of postoperative complications. Patients with complications had higher ‘Δ Albumin’ (0.6 g/dl vs. 0.27 g/dl, p =0.001) compared to those without complications. The ROC curve Area under the curve of Δ Albumin to discriminate patients with complications was 0.865. Cut-off value of ‘Δ Albumin’ ≥ 0.35 g/dl resulted in highest accuracy of 80.36%, sensitivity of 95.2% and specificity of 71.4%. Conclusion: Early postoperative fall in albumin level may identify patients at risk for overall as well as surgery specific complications after colorectal resections.